2020
DOI: 10.1109/access.2020.2986470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ICP Algorithm in 3D Point Cloud Registration

Abstract: The iterative closest point (ICP) algorithm is widely used in three-dimensional (3D) point cloud registration, and it is very stable and robust. However, its biggest drawback is being easily trapped in a local optimal solution, which results in the incorrect registration result. Currently, there is neither a clear effective range to define whether the ICP algorithm will fall into a local optimum nor a study providing a comprehensive evaluation of the ICP algorithm. In this paper, we take the overlap ratio, ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 94 publications
0
54
0
Order By: Relevance
“…The second adjusts the point cloud through the minimization of the distance between the point in the point cloud of reference and the tangent plane to its corresponding point in the point cloud to register. Studies shown that the validity of point-to-point ICP is more robust to Gaussian noise than point-to-plane ICP [60]. However, the latter undergoes fewer iterations, and it is more effective [60].…”
Section: Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The second adjusts the point cloud through the minimization of the distance between the point in the point cloud of reference and the tangent plane to its corresponding point in the point cloud to register. Studies shown that the validity of point-to-point ICP is more robust to Gaussian noise than point-to-plane ICP [60]. However, the latter undergoes fewer iterations, and it is more effective [60].…”
Section: Alignmentmentioning
confidence: 99%
“…Studies shown that the validity of point-to-point ICP is more robust to Gaussian noise than point-to-plane ICP [60]. However, the latter undergoes fewer iterations, and it is more effective [60]. Since the point clouds are cleaned and filtered from noise before starting the registration process, the point-to-point ICP method was chosen for this work.…”
Section: Alignmentmentioning
confidence: 99%
“…When a suitable model is present, model-driven building extraction is more robust (Li et al, 2020). For example, Karantzalos and Paragios (2008) proposed a set of building templates as shape priors to guide the segmentation of buildings from aerial imagery, achieving superior results to pure intensitybased segmentation.…”
Section: Building Extraction For Construction Sitesmentioning
confidence: 99%
“…Point cloud registration, e.g., the Iterative Closest Point (ICP) algorithm, aligns the point clouds to compute the rigid pose transformation. Despite its simplicity and efficiency, ICP requires a good initialization and is easily trapped in the local optimum [12]. Previous efforts have been made to improve ICP for the global optimal solution [13][14][15].…”
Section: Introductionmentioning
confidence: 99%